Recognition of an individual employed under the civil law contract as employee - Świątkowski, Andrzej Marian (Acta Universitatis Lodziensis. Folia Iuridica, 2019)
The author presents unified concept of worker in the UE employment law. It includes all groups of active population who perform dependent, personally and economically, during the certain period of time services for and under the direction of another person in return of remuneration. Under that UE autonomous concept of employment any type of services, including self employment regulated by the civil law, is protected against major risks caused by the globalization and poverty.